EFFECTIVENESS OF MULTI-SPECIES PLANTS (Canna indica and Echinodorus palaefolius) TO REDUCE ORGANIC MATTER AND PHOSPHATE (PO4) IN DOMESTIC WASTE - Ignasius Peis Ravysateles Meteray; Haryati Bawole Sutanto; Guruh Prihatmo (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
Domestic waste is the residue of household activities, one of which can be sourced from the campus. Domestic waste discharged into water bodies such as rivers can potentially increase the concentration of nutrients and pathogens in the water, so there is a need for an easy and affordable sewage treatment system to be implemented by the community. The Constructed Wetland system with subsurface flow planted with multi-species plants (Canna indica and Echinodorus palaefolius) can be an option to reduce the concentration of organic matter and phosphate (PO4) in domestic waste. Excessive organic matter and phosphate (PO4) in the water can increase the growth of aquatic plants and algae in the river, resulting in a decrease in dissolved oxygen and damage to the river ecosystem. This study aims to determine the ability of two plant species in one bioreactor with a Subsurface Constructed Wetland system to reduce Organic Material and Phosphate (PO4) levels. Parameters measured during this study were temperature, BOD, DO, pH, plant height and weight. The results of this study indicated that the Subsurface Constructed Wetland system with multi-species plants (Canna indica and Echinodorus palaefolius) had an organic matter reduction efficiency of 67.04% and Phosphate (PO4) of 66%